Modeling crustal structure of the south-eastern Fennoscandia - Pavlenkova, Ninel I; Pavlenkova, Galina A (Studia Geophysica et Geodaetica)
We present new seismic velocity models of the crust and uppermost mantle along two refraction and wide-angle reflection profiles in the southern Fennoscandia: the Pribalt and 1-EB profiles. Some new results obtained along the Coast and the Baltic Sea profiles are also presented. The intercept time method and ray tracing are used for the modeling. The study shows that the lateral variations are small in the velocity structure of’ the crust up to the depth of 20–25 km. The most significant lateral variations are observed in the Moho discontinuity topography and in the seismic velocities in the lower crust. In Paleoproterosoic Svekofennian domain, besides the well-known Moho depression in southern Finland, another Moho depression is revealed in the region from the Gotland Island to the Gulf of Riga. We suggest that this depression can correspond to the unknown crustal unit (we call it the Gotland-Riga belt). The Moho depth increases from the average of 40–45 km to 55 km in this belt. The Moho depression is filled by the matter with velocities of 6.8–7.1 km/s. Deep faults inclined to the north and strong variations of the mantle velocities are typical for the uppermost mantle of the Gotland-Riga belt. Ninel I. Pavlenkova, Galina A. Pavlenkova. Obsahuje seznam literatury